THE REPRESENTATION OF PATRIARCHAL IDEOLOGIES IN THE SHORT STORY “DAUGHTER OF THE BOOK” BY DAHLIA ADLER - Aura Hilda Haryono (MABASAN, 2024)
Literature represents and portrays variations in many aspects of life. It is a cultural product, meaning it comes from a process that aims to represent socio-cultural reality in a certain place and shows how literature and society are connected. Since it mirrors phenomena in real life, literature has many stories that relate to the community, including gender inequalities. Gender inequalities come from norms, values, stereotypes, structures, and systems that still believe that men should be ahead of women, allowing discrimination toward women. The idea that men are better than women are called patriarchal ideology. This article purposes to examine the patriarchal ideologies that Rebekah needs to deal with as a woman in the story “Daughter of the Book” by Dahlia Adler. To analyze the patriarchal ideologies in the story, the writer uses qualitative research to understand on the social phenomenon which happens in the society. The writer finds out three patriarchal ideologies found in the story. They are the “cult of ‘true womanhood’”, traditional gender role, and the objectification of women which exist in the society of Rebekah’s place.